Peningkatan Kreatifitas melalui Teknik Eco-Print pada Siswa Sekolah Dasar di Desa Jombor, Kecamatan Jumo, Kabupaten Temanggung - Nila Prasetya Aryani; Alfi Dian Muismi; Syahara Melani (BERDAYA Indonesian Journal of Community Empowerment, 2024)
This research aims to develop students' creativity in creating art using fabric media in the form of tote bags using eco print techniques. The ecoprint technique is a coloring technique using natural raw materials, for example using leaves, but the leaves used must be fresh, dry leaves. The leaves used are papaya leaves, cassava, ferns, kenikir. The method used in this research is a descriptive qualitative method located at SD N Jombor. This research was carried out by making initial observations regarding eco print-based learning. This observation technique is used to observe student activities in learning activities. At the implementation stage, researchers conduct training or practice directly the eco print process. The results of this research show that using the eco print technique can increase students' creativity through pattern preparation activities that produce interesting compositions.